Performance analysis of Brazilian Depositary Receipts (BDRs) in the period from 2018 to 2022 - Enes, Wilson Machado (2023)
The general objective of the study is to analyze the performance of a set of BDRs selected in a non-probabilistic way in the period from 2018 to the first half of 2022. representative of foreign companies in the national market, in the face of a pandemic scenario and with the specific objective of observing the effects on the trading volume of these products in accordance with resolution CVM Nº 3. such assets. To analyze the performance of the BDRs, a sample of 6 companies was selected, covering the technology, cyclical consumption and health sectors, in which a descriptive analysis of the indices used was implemented, comparing two periods, the pre-pandemic that encompasses the years 2018 and 2019 and the pandemic moment between 2020 and the first half of 2022. In addition, the study is complemented by applying the Student's t hypothesis test for normal data and the Mann-Whitney test for those that do not adhere to the normal distribution, validating whether the The pandemic actually impacted the behavior of the analyzed economic-financial performance indices. Therefore, the results obtained allowed to construct and observe the effects on the researched indices to the detriment of the COVID-19 action in a set of visual data contained in graphs and tables and also to infer that from the hypothesis tests applied to dry liquidity and the debt ratio were the ratios that rejected the null hypothesis and, therefore, were impacted by the economic shock that occurred.